HUBUNGAN KELINCAHAN DAN KECEPATAN DENGAN KETERAMPILAN MENGIRING BOLA PADA TEAM SEPAKBOLA PUTRA PPLP DISPORA RIAU PEKANBARU - Yulki Musliadi; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine whether there is a relationship thebetween agility and speed dribbling skills on men's football team PPLPDispora Riau. The forms of this research are the correlation study, the population in this study from the men's football team PPLP Dispora Riau, and the sample in this study is the men's football team PPLP Dispora Riauwhich have numbered 18 people. The first analysis in the calculation of the relationship between X1 and Y, where rtab at significant level α (0,05) = 0.482 mens rhutung (0.504)> rtab (0,482), which means the hypothesis is accepted and there is a meaningful relationship between agility with dribbling skills on the men’s football team of PPLP Dispora Riau, a second analysis of speed (X2) with dribbling skills (Y), where rtab at significant level α (0,05) = 0.482 means rhitung (0.607)> rtab (0,482), which means the hypothesis is accepted and there is a relationship the between the dribbling ability in men's football team PPLP Dispora Riau, the analysis of the three relationships agility (X1)and speed (X2) with the dribble (Y) was obtained, which rtab at significant level α (0,05) = 0.482 , means rhitung (0.634)> rtab (0,482). Then it can be concluded that the relationship between (X1) and (X2) premises Y or the relationship between the agility and speed dribbling skills are significant. Thus that the soccer athlete dribbling ability from men’s football team of PPLP Dispora Riau in the forecast with their agility and speed.Keywords: Speed, agility and dribbling skills